GMC evolution in a barred spiral galaxy with star formation and thermal feedback. Issue 2 (20th June 2016) - Fujimoto, Yusuke; Bryan, Greg L.; Tasker, Elizabeth J.; Habe, Asao; Simpson, Christine M.
Abstract: We explore the impact of star formation and thermal stellar feedback on the giant molecular cloud population forming in a M83-type barred spiral galaxy. We compare three high-resolution simulations (1.5 pc cell size) with different star formation/feedback models: one with no star formation, one with star formation but no feedback, and one with star formation and thermal energy injection. We analyse the resulting population of clouds, finding that we can identify the same population of massive, virialized clouds and transient, low-surface density clouds found in our previous work (that did not include star formation or feedback). Star formation and feedback can affect the mix of clouds we identify. In particular, star formation alone simply converts dense cloud gas into stars with only a small change to the cloud populations, principally resulting in a slight decrease in the transient population. Feedback, however, has a stronger impact: while it is not generally sufficient to entirely destroy the clouds, it does eject gas out of them, increasing the gas density in the intercloud region. This decreases the number of massive clouds, but substantially increases the transient cloud population. We also find that feedback tends to drive a net radial inflow of massive clouds, leading to an increase in the star formation rate in the bar region. We examine a number of possible reasons for this and conclude that it is possible that the drag force from the enhanced intercloud density could be responsible.